Równania Statyczne Odkształcenia Płyt Sprężonych o Zmiennej Grubości - Dzieniszewski, W. (Engineering Transactions, 1966)
The object of the considerations are plates of any form and variable thickness, undergoing finite vertical displacement and interconnected in two directions by means of elements of any form, ex and ey, constituting in the horizontal plane two orthogonal sets kx and ky. The elements are prestressed with the forces Sx and Sy of any distribution in the closed region of the plate. The continuity equation (3.6) and the six equilibrium equations (4.1) and (4.2) in the deformed state are reduced to two equations (5.4) with partial derivatives with respect to the unknown functions F and w describing the state of stress and strain of the plates. The boundary conditions are formulated for the fundamental types of edge support. The equations contained in this paper will constitute a basis for the next paper devoted to the design problem of prestressed plates.